El mascarón arquitectónico preclásico de la Estructura 3 de Chacté, Guatemala - Carlos Morales-Aguilar; Daniel Salazar Lama; Ivan Šprajc; Richard D. Hansen (Journal de la Société des Américanistes)
Recent archaeological investigations carried out at the Maya site of Chacté, a peripheral architectural suburb of the ancient city of El Mirador, located in northern Guatemala, revealed an important occupation of the Late Preclassic (ca. 350 BC), a period in which El Mirador and its allied centers reached their peak in cultural development and socio-political terms. Chacté represents a part of this development by constructing a ceremonial center with large plazas and elite buildings. The site was also linked to the great center of El Mirador by a 4 km-long causeway. Archaeological excavations in Chacté focused on Structure 3, the eastern building of an E-Group complex, where an important Preclassic sculpture mask was found. In this paper, we offer a preliminary iconographic interpretation of this sculpture mask that might represent the K’inich Ajaw god, symbolizing the emergence of the sun in the east.